Introduction: Towards the understanding of the role of cognition in Indo-Tibetan Buddhism - Korobov, Vladimir (Acta Orientalia Vilnensia, 2010)
SPECIAL THEME: THROUGH THE LOOKING-GLASS OF THE BUDDHA-MIND: STRATEGIES OF COGNITION IN INDO-TIBETAN BUDDHISM